"I am concerned with the future of my children": the project economy and shifting views of education in a Tibetan pastoral community. Issue 1 (2nd January 2019) - Gyal, Huatse
ABSTRACT: Tibetan pastoralists have been subject to large-scale state-led development policies over the past three decades. The provisioning of institutionalized state schooling, in particular, has all along been part and parcel of these development projects, including urbanization and resettlement initiatives. However, for a variety of reasons, the promotion of schooling in Tibetan pastoral areas has been a challenge since the first Maoist efforts in 1950s. By focusing on a case study of a Buddhist monk's persistent effort to build a primary school in his home village in the eastern region of Tibet in 1990, and on how Tibetan villagers' views of him and his school project have changed over time, this paper examines the nexus of relationships between schooling, and social and cultural changes in pastoral Tibet. I also aim to relate Tibetan pastoralists' shifting values of schooling to the larger social and political context, particularly the ubiquitous Chinese xiangmu (project) economy and Tibetan pastoralists' ever-increasing dependence on the state. This paper argues that although state schooling is highly contested, it has been one of the driving forces of social change in Tibetan pastoral areas today.